Internalizing Character Values Through Boarding School Culture: Evidence from Congregational Tahajjud Practices in an Indonesian Pesantren - A. Hasyim; Syamsul Rijal (Journal of Islamic Education Research, 2026)
This study investigates how character values are internalized through boarding school culture by examining congregational tahajjud practices in an Indonesian pesantren. The purpose of the study is to explore the role of collective night prayer as a cultural and educational mechanism for cultivating students’ character and to identify the factors that support and hinder this process. A qualitative case study approach was employed at the Nahdlatut Ta'limiyah Islamic Boarding School in Plakpak, Pegantenan, Pamekasan, Indonesia. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using data reduction, data display, and conclusion-drawing procedures. The findings reveal that congregational tahajjud functions not merely as a religious ritual but as a culturally embedded practice that facilitates the internalization of discipline, independence, patience, sincerity, and noble character among students. A supportive religious environment, exemplary leadership from religious teachers, continuous habituation, and active student participation strengthen the process. At the same time, challenges arise from difficulties in adapting for new students, diverse family backgrounds, and the influence of modern technology. The novelty of this study lies in its emphasis on congregational tahajjud as a cultural mechanism of character formation within the pesantren tradition. This study contributes to the literature on Islamic education, character education, and boarding school culture by demonstrating how religious practices can transform spiritual values into enduring behavioral dispositions.